2016
DOI: 10.1155/2016/4841756
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals Xyr1 as a Transcription Factor Regulating Gene Expression beyond Carbohydrate Metabolism

Abstract: Xyr1 has been demonstrated to be the main transcription activator of (hemi)cellulases in the well-known cellulase producer Trichoderma reesei. This study comprehensively investigates the genes regulated by Xyr1 through RNA sequencing to produce the transcription profiles of T. reesei Rut-C30 and its xyr1 deletion mutant (Δxyr1), cultured on lignocellulose or glucose. xyr1 deletion resulted in 467 differentially expressed genes on inducing medium. Almost all functional genes involved in (hemi)cellulose degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
5
21
1
Order By: Relevance
“…Both proteins have a carbohydrate-binding domain that belongs to family 1 (CBM1), and one XBS was predicted in each gene promoter. Therefore, they play a role in bagasse deconstruction and are transcriptionally regulated by Xyr1, as reported previously (Reithner et al, 2014 ; Ma et al, 2016 ). In addition, 14 putative sugar transporters, three Zn2Cys6 transcriptional regulators, one putative GCN5-acetyltransferase, one methyltransferase and several other genes were also co-expressed with xyr1 and had XBS in their promoters (Figure 4A , Table S8 ).…”
Section: Resultssupporting
confidence: 76%
“…Both proteins have a carbohydrate-binding domain that belongs to family 1 (CBM1), and one XBS was predicted in each gene promoter. Therefore, they play a role in bagasse deconstruction and are transcriptionally regulated by Xyr1, as reported previously (Reithner et al, 2014 ; Ma et al, 2016 ). In addition, 14 putative sugar transporters, three Zn2Cys6 transcriptional regulators, one putative GCN5-acetyltransferase, one methyltransferase and several other genes were also co-expressed with xyr1 and had XBS in their promoters (Figure 4A , Table S8 ).…”
Section: Resultssupporting
confidence: 76%
“…Unlike the previously reported studies [ 11 ], our recent study indicated that most of these β-glucosidase genes were upregulated by Xyr1 in the inducing medium (wheat bran and Avicel); however, a β-glucosidase gene named bgl3i ( cel3g ) was downregulated [ 12 ]. On the contrary, the expression level of bgl3i was upregulated in a xyr1 deletion strain [ 12 ]. Recently, the enzyme activities of the heterologously expressed BGL3I from Aspergillus oryzae to different substrates have been compared with other β-glucosidases of T. reesei [ 18 ].…”
Section: Introductioncontrasting
confidence: 65%
“…The bgl3i gene is composed of four exons and three introns, as predicted in JGI (Transcript ID: TRIRE2_47268), and belongs to the GH3 family according to the Pfam database. It was screened using the expression profile data of our laboratory, based on the significantly increased transcription in the xyr1 disrupted strain compared with the WT under induction conditions [ 12 ]. The expression profile data and the cDNA sequence of bgl3i showed that the sites of its start codons and exon/intron junctions were not properly located on the JGI website, but were correct on NCBI (accession no.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations